Commodity trade between Pakistan and the US: is there evidence of the J-curve?. Issue 11 (2nd March 2016) - Bahmani-Oskooee, Mohsen; Iqbal, Javed; Nosheen, Misbah
ABSTRACT: A few studies that have attempted to estimate the short-run (J-curve) and long-run impact of exchange rate depreciation on Pakistan's trade balance are either based on aggregate trade data between Pakistan and the rest of the world or between Pakistan and her bilateral trading partners. The findings are mixed at best. Considering the trade balance between Pakistan and the US, as one of its major partners, no significant effects have been discovered. Suspecting that the trade flows between the two countries could suffer from another aggregation bias, we disaggregate their trade flows by commodity and consider the trade balance of 45 industries that trade between the two countries. We find significant short-run effects of currency depreciation on the trade balance of 17 industries. The short-run effects last into the long run in 15 cases. The largest industry that account for more than 10% of the trade seems to benefit from real depreciation in the long run.